Identifying and Addressing Risks in the Early Design of a Sociotechnical System through Premortem. (September 2022) - Bettin, Briana; Steelman, Kelly S.; Wallace, Charles; Pontious, Dana; Veinott, Elizabeth S.
Anticipating risks in software development is always challenging, but particularly so when the software application is part of a novel sociotechnical system with various human and physical components. Our interdisciplinary team of software engineering and human factors researchers is designing such a system. In order to identify and mitigate the risks latent in this previously unexplored space, we have used the premortem method at an early stage in system design. In the premortem, the team ideated failure scenarios across the range of system use, then collaborated on ways to eliminate, mitigate, or monitor the risks of these failures. We have found the premortem method valuable in recognizing and mitigating previously unanticipated risks and in enriching team communication.